Development and usability testing of an electronic patient-reported outcome measure (ePROM) system for patients with advanced chronic kidney disease. (1st October 2018) - Aiyegbusi, Olalekan Lee; Kyte, Derek; Cockwell, Paul; Marshall, Tom; Dutton, Mary; Walmsley-Allen, Natalie; Auti, Ram; Calvert, Melanie
Abstract: Background: Chronic kidney disease (CKD) is a long-term medical condition associated with symptoms which may negatively impact on patients' health-related quality of life (HRQOL). Patient-reported outcome (PRO) measures or questionnaires may be used to capture symptoms/HRQOL experienced by patients with advanced CKD. Method: Two PRO questionnaires were electronically adapted and incorporated in an electronic system developed at University Hospitals Birmingham NHS Foundation Trust (UHB), Birmingham. Usability testing was conducted with patients with advanced CKD. Qualitative methodology was used to elicit participants' views. Results: Participants had a mean age of 64.3 years (range: 36–87 years). All owned electronic devices and had access to the internet. The mean time required to complete the two electronic questionnaires was 15.9 min (range = 8–34 min). Patients who had difficulties with the system were those who had the least experience of using the internet and electronic devices. The average usability and satisfaction score was 4.6 (5-point scale). Conclusions: Our study suggests that individuals with advanced CKD may find the Renal ePROM system acceptable and easy to use. The use of the Renal ePROM may complement clinician-reported outcomes and assist with the management of patients with advanced CKD. Highlights: A renal ePROM system may assist clinicians with the management of patients with advanced chronic kidney disease. Usability testing is crucial during the development of an ePROM system for older patients with chronic medical conditions. Patients with advanced CKD may find the system acceptable for reporting their symptoms and health-related quality of life. Some individuals may experience dexterity issues and family members may influence the use of the system real life. Individuals within this age group may unwittingly under-report their engagement with information technology.